Analisis Penyelesaian Wanprestasi dalam Pembiayaan Murabahah - Yeni Widiyaningsih; Felina Dwi Wulandari; Putri Khoirin Nida; Aida Rahma; Wahidullah Wahidullah (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
In the context of murabahah financing, default (wanprestasi) is a common issue that can lead to losses for Islamic banks. According to the Fatwa of the National Sharia Council MUI No. 43/DSN-MUI/VIII/2004, dhaman or compensation can be imposed on customers who fail to meet their payment obligations as stipulated in the contract. This study employs a qualitative descriptive method to analyze the mechanism of dhaman and its implications for customers experiencing default. The findings indicate that banks have the right to impose penalties in the form of fines (ta'zir) and/or compensation (dhaman) on customers who are able to pay but are late in fulfilling their obligations. However, it is recommended that Islamic banks first offer restructuring options to customers before taking further action. This research emphasizes the need for a balance between protecting customer rights and the bank's interests to achieve fairness in Islamic banking practicef.